Language and Communication Competences, the Key to Quality Education - Mª Victoria Reyzábal (Universidad Autónoma de Madrid, 2016)
The development of communicative competences as well as of those specifically  linguistic is basic to be fluent in all the other competences, so it is fundamental to work them through a rigorous educational curriculum, that sequences their gradual acquisition and to assess their achievement in a continuous and formative way. In this context, textual competence −oral and written− and the management of non verbal languages become essential.  Without a successful, correct, consistent and appropriate communication, the human being looses cognitive nuances, is deprived of fully understanding of reality and interact socially in a limited way.